2009
DOI: 10.1111/j.1440-1819.2008.01886.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 10‐week weight control program on obese patients with schizophrenia or schizoaffective disorder: A 12‐month follow up

Abstract: Aims:  Weight gain secondary to antipsychotic medication is associated with many serious conditions, including type II diabetes mellitus, hypertension, and coronary heart disease, and also with poor medication compliance. Weight control programs may be of benefit to outpatients with schizophrenia, but also raise an issue of cost‐effectiveness. We aimed to evaluate the effectiveness of a 10‐week weight control program for outpatients taking atypical antipsychotics for treatment of schizophrenia, and to follow u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
2
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 26 publications
6
51
2
2
Order By: Relevance
“…106 A Taiwanese study of 33 patients with schizophrenia demonstrated a mean 3.7 kg and 2.7 kg reduction in body weight after 6 months and 1 year, respectively, following a 10week multimodal weight control programme. 107 Weight loss was achievable with ongoing support in a long term (8 years) observational study of a group intervention in wellmotivated people with SMI (Box 1). 108 Progressive reductions in mean weight and BMI occurred through out followup with no suggestion of a plateau.…”
Section: Lifestylementioning
confidence: 99%
“…106 A Taiwanese study of 33 patients with schizophrenia demonstrated a mean 3.7 kg and 2.7 kg reduction in body weight after 6 months and 1 year, respectively, following a 10week multimodal weight control programme. 107 Weight loss was achievable with ongoing support in a long term (8 years) observational study of a group intervention in wellmotivated people with SMI (Box 1). 108 Progressive reductions in mean weight and BMI occurred through out followup with no suggestion of a plateau.…”
Section: Lifestylementioning
confidence: 99%
“…Little is known about the effect of weight loss programs on mental health outcomes in other psychiatric disorders such as schizophrenia, bipolar and anxiety disorders. However, in a study by Chen et al (2009) on patients with schizophrenia and antipsychotic-related obesity, participation in a 10-week multimodal weight control program led to weight loss that was mostly maintained at 12-months follow up. Completers also reported significant improvements in measures of quality of life, general health, bodily pain, depression and other emotional subscales.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In a meta-analysis on randomised, controlled, cognitive-behavioural weight loss trials, Bonfioli et al (2012) concluded that in patients with psychosis, a weight loss of 0.98 points in BMI (corresponding to a loss of 3.12% of initial weight) was demonstrated from pooled data. Weight loss programs can also prevent weight gain associated with antipsychotic use and even promote weight loss (Chen et al, 2009, Gabriele et al, 2009, Menza et al, 2004, Vreeland et al, 2003. In a study by Zhang et al (2012), patients with psychotic spectrum disorders experienced a greater percent baseline weight loss at 12 months, and greater percent BMI loss at 9 and 12 months than people suffering from other psychiatric disorders and no psychiatric disorder.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Its results are similar to those reported by other studies of weight loss interventions, which found a mean loss of 4.3±5.6 pounds (5). Participants in the RENEW program had maintained their weight loss at six months; other studies indicate that individuals with serious mental illness who have participated in weight loss programs have maintained their weight loss for up to one year (8,9). A subgroup of RENEW participants lost 5% to 10% of body weight, an achievement that is associated with important health benefits such as reduced risk of diabetes and high blood pressure (10).…”
Section: Discussionmentioning
confidence: 99%